The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1111/j.1468-0262.2002.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Informational Size and Incentive Compatibility

Abstract: We examine a general equilibrium model with asymmetrically informed agents. The presence of asymmetric information generally presents a conflict between incentive compatibility and Pareto efficiency. We present a notion of informational size and show that the conflict between incentive compatibility and efficiency can be made arbitrarily small if agents are of sufficiently small informational size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
62
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 11 publications
(11 reference statements)
5
62
0
Order By: Relevance
“…It is well-known, however, that truthful revelation is generally no longer incentive compatible when we move from a private values environment to an interdependent values environment. In McLean and Postlewaite (2014) (henceforth MP (2014)) we showed that, when agents are informationally small in the sense of McLean and Postlewaite (2002), there exists a modi…cation of a generalized VCG mechanism using small additional transfers that restores incentive compatibility. This paper presents an alternative, two-stage non-direct mechanism that accomplishes the same goal -restoring incentive compatibility for interdependent value problems.…”
Section: Introductionmentioning
confidence: 92%
“…It is well-known, however, that truthful revelation is generally no longer incentive compatible when we move from a private values environment to an interdependent values environment. In McLean and Postlewaite (2014) (henceforth MP (2014)) we showed that, when agents are informationally small in the sense of McLean and Postlewaite (2002), there exists a modi…cation of a generalized VCG mechanism using small additional transfers that restores incentive compatibility. This paper presents an alternative, two-stage non-direct mechanism that accomplishes the same goal -restoring incentive compatibility for interdependent value problems.…”
Section: Introductionmentioning
confidence: 92%
“…It is well-known, however, that truthful revelation is generally no longer incentive compatible when we move from a private values environment to an interdependent values environment. In McLean and Postlewaite (2014) (henceforth MP (2014)) we showed that, when agents are informationally small in the sense of McLean and Postlewaite (2002), there exists a modi…cation of a generalized VCG mechanism using small additional transfers that restores incentive compatibility. This paper presents an alternative, two-stage, mechanism that accomplishes the same goal -restoring incentive compatibility for interdependent value problems.…”
Section: Introductionmentioning
confidence: 92%
“…It is well-known, however, that truthful revelation is generally no longer incentive compatible when we move from a private values environment to an interdependent values environment. In McLean and Postlewaite (2014) (henceforth MP (2014)) we showed that, when agents are informationally small in the sense of McLean and Postlewaite (2002), there exists a modification of a generalized VCG mechanism using small additional transfers that restores incentive compatibility. This paper presents an alternative, two-stage non-direct mechanism that accomplishes the same goal -restoring incentive compatibility for interdependent value problems.…”
Section: Introductionmentioning
confidence: 92%